Setting Risk Limits and Ensuring Fairness in Learning Health Care. Issue 3 (28th June 2022) - Wendler, David; Sullivan, Connor
Abstract: Historical abuses resulted in the segregation of clinical research and clinical care. While this approach has protected participants, it is extremely inefficient, leading commentators to propose (re)integrating research and care into learning health care systems. Previous commentators have argued that, in these systems, it could be appropriate to condition care on patients' consent to participation in research, but only when the added research risks are minimal. In the article "Compulsory Research in Learning Health Care: Against a Minimal Risk Limit, " Robert Steel agrees about making research participation a condition for receiving care in these systems, but he argues that the limit to minimal risks is unfounded, and he offers compelling reasons to think that, in principle, permitting greater research risks could be fair and consistent with individual rights. Unfortunately, the nature of current institutions suggests that this approach is unlikely to be implemented fairly. We conclude that, to ensure fair learning health care systems, research and care may need to be reformed in more fundamental ways .